Covalent organic framework membrane for waste acid recovery and power generation as well as preparation method and application of covalent organic framework membrane
Through the design and preparation of covalent organic frame membrane materials, the problem of difficulty in achieving waste acid recycling and permeability power generation in the prior art is solved, and ultra-fast transmission of H+ and efficient interception of other ions is achieved, and the efficiency of process application is improved.
Patent Information
- Application Number
- CN202411779524.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The prior art is difficult to achieve a balance between waste acid recycling and permeability power generation, and it is impossible to achieve efficient recycling and power generation of waste acid resources at the same time.
The PaTp composite layer was formed by polymerizing paraphenylenediamine and trialdehyde phthalglucoside at the surface interface of the substrate using covalent organic frame film materials, and a PaTp-TMC film was obtained by modification of phenylenediamine, trialdehyde phthalglucoside, which achieved ultra-fast transmission of H+ and efficient interception of other ions.
It realizes ultra-fast transmission of H+ and efficient interception of other ions, can complete waste acid recycling and power generation at the same time, improves the efficiency of process application, and has a simple preparation process and good durability.
Smart Images

Figure CN119656887A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wastewater separation and recovery, and in particular to a covalent organic framework membrane that can be used for waste acid recovery and power generation, and a preparation method and application thereof. Background Art
[0002] In industrial production processes such as metal smelting, etching and mining, a large amount of inorganic acids such as hydrochloric acid, sulfuric acid and nitric acid are needed to clean the metal surface or extract metal components. If the waste acid generated in these processes is discharged directly without treatment, it will not only pose a huge threat to the environment, but also cause a huge waste of resources. Therefore, the resource recovery of waste acid has become the main trend of waste acid treatment. Osmotic energy is a renewable clean energy with abundant reserves and easy access. The most common osmotic power generation comes from the mixing of river water and seawater. However, it is generally overlooked that acidic industrial wastewater can also be used for osmotic power generation. In particular, the acidic wastewater discharged from chemical plants contains a large number of protons and various inorganic ions, which provides a prerequisite for the acquisition of osmotic energy based on proton gradient.
[0003] Traditional methods for treating waste acid include neutralization precipitation, distillation, solvent extraction, and membrane treatment. Among them, membrane treatment technology has the advantages of low energy consumption, small equipment footprint, and high separation efficiency. It is widely used in wastewater treatment, but it has problems such as secondary pollution, high energy consumption, and cumbersome operation. In recent years, two-dimensional nanofluid channel membrane materials prepared by the inspiration of electric eel ion channel proteins have shown excellent energy conversion performance. Sun et al. designed a membrane with uniform angstrom-level pores and built-in charge-assisted hydrogen bond donors, which can preferentially conduct HCl, while the conductivity of other compounds is almost negligible. The COFMs synthesized by Banerjee et al. have high application value in sulfuric acid recovery. Wang et al. reported a RED device based on a two-dimensional (2D) layered Ti3C2Tx MXene membrane for collecting osmotic energy from industrial wastewater with a proton gradient. However, there is a restrictive relationship between the permeability and separation performance of the membrane materials currently reported for acid wastewater recovery or osmotic energy collection, and only one of the two applications of waste acid resource recovery or power generation using acidic solutions can be achieved. In view of this, it is necessary to provide a new separation membrane material to solve the balance problem between high permeability and high selectivity, and to simultaneously realize the two processes of waste acid resource recovery and power generation (i.e., osmotic energy conversion). Summary of the invention
[0004] In view of the deficiencies of the prior art, the first object of the present invention is to provide a method for preparing a covalent organic framework membrane that can be used for waste acid recovery and power generation.
[0005] The second object of the present invention is to provide a covalent organic framework membrane that can be used for waste acid recovery and power generation.
[0006] The third object of the present invention is to provide an application of a covalent organic framework membrane that can be used for waste acid recovery and power generation.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a covalent organic framework membrane that can be used for waste acid recovery and power generation, comprising the following steps:
[0009] (1) dissolving p-phenylenediamine (Pa) in ultrapure water to obtain solution A, and dissolving trialdehyde phloroglucinol (Tp) and trimesoyl chloride (TMC) in n-hexane to obtain solutions B and C, respectively;
[0010] (2) Solution A is dropped onto the surface of the PES membrane to form a Pa layer; then solution B is added dropwise to react with Pa to form a Pa Tp composite layer; finally solution C is added dropwise to react with the Pa Tp composite layer to form a Pa Tp-TMC membrane, and excess solution is removed;
[0011] (3) solidification to obtain a covalent organic framework membrane that can be used for waste acid recovery and power generation and is stored in ultrapure water.
[0012] Furthermore, in step (1), the mass fraction of p-phenylenediamine in the solution A is 1-3%, the mass fraction of trialdehyde phloroglucinol in the solution B is 0.01-0.1%, and the mass fraction of trimesoyl chloride in the solution C is 0.1-0.3%.
[0013] Furthermore, in step (2), the PES membrane is soaked in ultrapure water before adding solution A, and the soaking time is 12-36 hours.
[0014] Furthermore, in step (2), the volume ratio of solution A, solution B and solution C is (12-18):(7-13):(7-13), preferably 15:10:10.
[0015] Furthermore, in step (2), the residence time of the solution A on the surface of the PES membrane is 10-40 s, preferably 30 s.
[0016] Furthermore, in step (2), the reaction time of solution B and Pa is 5-15s, preferably 10s.
[0017] Furthermore, in step (2), the reaction time of the solution C and the Pa Tp composite layer is 10-40 s, preferably 30 s.
[0018] Furthermore, in step (3), the curing temperature is 70-90°C, preferably 80°C; and the curing time is 3-7 minutes, preferably 5 minutes.
[0019] In a second aspect, the present invention provides a covalent organic framework membrane that can be used for waste acid recovery and power generation, which is prepared according to the preparation method described in the first aspect.
[0020] Furthermore, the covalent organic framework membrane that can be used for waste acid recovery and power generation includes: a PES membrane substrate, and a PaTp-TMC membrane formed by forming a PaTp composite layer on the surface of the substrate with Pa and Tp and then modified with TMC.
[0021] Furthermore, in the covalent organic framework membrane that can be used for waste acid recovery and power generation, the thickness of the Pa Tp-TMC membrane is 0.7-3.4 μm, preferably 2-2.5 μm, and more preferably 2.4 μm.
[0022] In a third aspect, the present invention provides the use of the above-mentioned covalent organic framework membrane that can be used for waste acid recovery and power generation, including using it for waste acid recovery and power generation.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a covalent organic framework membrane that can be used for waste acid recovery and power generation. The membrane is prepared by polymerizing p-phenylenediamine and trialdehyde phloroglucinol at the interface of a substrate surface to form a PaTp composite layer, and then modifying the PaTp-TMC membrane with trimesoyl chloride. The covalent organic framework membrane has high selectivity and can achieve H + The ultrafast transport of ions and the efficient retention of other ions can simultaneously complete the two processes of waste acid recovery and power generation (osmotic energy conversion), greatly improving the efficiency of process applications.
[0025] 2. The covalent organic framework membrane of the present invention, which can be used for waste acid recovery and power generation, has high selectivity due to the sub-nano channels of the PaTp-TMC membrane. By modifying PaTp with TMC, the pore size of the obtained covalent organic framework membrane can be made smaller, increasing the affinity with H + binding site, thereby achieving H + The ultrafast transport of ions and the efficient retention of other ions have great potential in the recovery of waste acid.
[0026] 3. The covalent organic framework membrane that can be used for waste acid recovery and power generation of the present invention is prepared by a casting method, which has a simple process, mild conditions, simple instruments and easy operation. It can be prepared over a large area without subsequent chemical treatment, is green and environmentally friendly, and can be used for industrial production.
[0027] 4. Compared with the traditional waste acid recovery technology, the covalent organic framework membrane of the present invention which can be used for waste acid recovery and power generation does not require heating energy consumption in waste acid recovery, has low requirements for high temperature resistance and chemical corrosion resistance of the membrane, and exhibits excellent durability in the separation process; and in the osmotic energy conversion and collection process, the device used is simple and easy to assemble, and the test method is universal. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The invention relates to a method for preparing a covalent organic framework membrane for waste acid recovery and power generation.
[0029] Figure 2 Optical photograph of a covalent organic framework membrane for waste acid recovery and power generation.
[0030] Figure 3 This is the infrared spectrum of the covalent organic framework membrane used for waste acid recovery and power generation; Figure a is the infrared spectrum of three monomers, and b is the local infrared spectrum of PaTp / PES and PaTp-TMC / PES membranes.
[0031] Figure 4 SEM images of covalent organic framework membranes of different thicknesses used for waste acid recovery and power generation.
[0032] Figure 5 Schematic diagram of the covalent organic framework structure of different modified monomers used for waste acid recovery and power generation.
[0033] Figure 6 Schematic diagram of the permeation experiment for waste acid recovery; the left side is the feed side and the right side is the permeate side.
[0034] Figure 7 This is a physical picture of the device used for waste acid recovery and power generation applications.
[0035] Figure 8 The figure is a physical picture of the recovery and power generation performance test of the simulated waste acid solution before and after; in the figure, a is the raw material of the simulated waste acid solution, b is the original simulated waste acid solution, c is the simulated waste acid solution after filtering out excess sediment (for subsequent performance testing), and d is the clarified solution after the permeation test.
[0036] Fig. 9 The performance test results of waste acid recovery and power generation applications; a is the output power density measured in 50 times simulated waste acid solution, b is the ion concentration in the permeate solution measured after 5h of permeation after power generation test, and c is the H + , Cu 2+ The permeability and H + / Cu 2+ selection ratio. DETAILED DESCRIPTION
[0037] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0038] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0039] Example 1
[0040] A method for preparing a covalent organic framework membrane that can be used for waste acid recovery and power generation (the flow chart is as follows Figure 1 As shown), comprising the following steps:
[0041] (1) Soak the PES membrane in ultrapure water for 24 hours and set aside;
[0042] (2) dissolving p-phenylenediamine (Pa) in ultrapure water to obtain a solution A with a mass fraction of 2%, and dissolving trialdehyde phloroglucinol (Tp, 0.05 wt %) and a modified monomer trimesoyl chloride (TMC, 0.2 wt %) in n-hexane to obtain a solution B with a mass fraction of 0.05% and a solution C with a mass fraction of 0.2% respectively;
[0043] (3) 15 mL of solution A was dropped onto the surface of the PES membrane for 30 seconds to form a Pa layer; then solution B was added dropwise to react with Pa for 10 seconds to form a PaTp composite layer; finally solution C was added dropwise to react with the Pa Tp composite layer for 30 seconds to form a PaTp-TMC membrane, and the excess solution was removed;
[0044] (4) After removing the excess organic solution, the obtained film was cured at 80°C for 5 min to obtain a covalent organic framework film, which was denoted as PaTp-TMC / PES. The optical photograph of the obtained film is shown in Figure 2 , presenting as a shiny orange-yellow film.
[0045] The PaTp-TMC / PES obtained in this example was characterized by infrared spectroscopy. Figure 3 As shown in the figure, after TMC modification, 1650cm -1 A new peak appeared at , which was attributed to the C=O stretching vibration of the amide group, proving the success of the modification.
[0046] Comparative Example 1
[0047] The difference between Comparative Example 1 and Example 1 is that the amounts of solution A, solution B, and solution C are different, as shown in Table 1 below, and PaTp-TMC / PES membranes with different thicknesses are prepared, and their SEM images are shown in Figure 4 shown.
[0048] Table 1
[0049] Group Volume of solution A, mL Volume of solution B, mL Volume of solution C, mL membrane Example 1 15 10 10 <![CDATA[Pa 15 Tp 15 -TMC 10 / PES]]> Comparative Example 1-1 9 6 6 <![CDATA[Pa9Tp6-TMC6 / PES]]> Comparative Example 1-2 3 2 2 <![CDATA[Pa3Tp2-TMC2 / PES]]>
[0050] Comparative Example 2
[0051] The difference between Comparative Example 2 and Example 1 is that the types of modified monomers are different. The structural diagram is as follows Figure 5 See the table below for details.
[0052] Table 2
[0053] Group Modified monomer membrane Example 1 TMC PaTp-TMC / PES Comparative Example 2-1 Terephthaloyl chloride TPC PaTp-TPC / PES Comparative Example 2-2 Benzoyl chloride BZC PaTp-BZC / PES Comparative Examples 2-3 \ PaTp / PES
[0054] Test Example 1: Penetration Test
[0055] In a typical experiment, the membrane sealed with parafilm is placed in the middle of an H-type cell (e.g. Figure 6 ), the feed solution (1M HCl / KCl solution) and ultrapure water are added to the left and right sides of the cell respectively. At regular intervals, all the ultrapure water on the permeation side (right side) is taken out for testing. At the same time, the same volume of ultrapure water as that on the feed side (left side) is added to the permeation side to maintain continuous permeation. The proton and cation concentrations on the permeation side are detected by a pH meter and an inductively coupled plasma mass spectrometer (ICP-MS), respectively. The ion permeation rate (P i , mol m -2 h -1 ) is calculated as shown in the following formula (I):
[0056] P i =(ΔC×V) / (A×Δt) (I)
[0057] Among them, ΔC (mol L -1 ) is the ion concentration on the permeate side, V(L) is the effective volume of the permeate solution, A(m 2 ) is the effective penetration area, and Δt(h) is the penetration time.
[0058] The various films obtained in the above examples and comparative examples were tested according to the above method, and the results are shown in Table 3 below.
[0059] Table 3
[0060] Group <![CDATA[H + / K + Select ratio]]> <![CDATA[H + Permeation flux (mol m -2 h -1 )]]> Example 1 451 6.72 Comparative Example 1-1 55 2.40 Comparative Example 1-2 10 1.15 Comparative Example 2-1 61 3.31 Comparative Example 2-2 3 1.56 Comparative Examples 2-3 1 1.10
[0061] The results show that the thickness of the PaTp-TMC / PES membrane in Example 1 is different from that in Comparative Example 1.+ / K + The selectivity difference is significant, and the PaTp-TMC / PES membrane obtained in Example 1 has the highest selectivity.
[0062] Compared with Comparative Example 2, the performance of the PaTp-TMC / PES membrane obtained in Example 1 is the best, maintaining H + / K + The highest selectivity was obtained by the PaTp-TPC / PES membrane. In contrast, the selectivity of the PaTp-BZC / PES and PaTp / PES membranes was lower, but the modified PaTp-BZC / PES was slightly better than the original PaTp / PES. Therefore, the TMC of the present invention was selected as the modified monomer to obtain a membrane with better selectivity and permeation flux.
[0063] In order to investigate the effect of the concentration of HCl / KCl solution, this experiment tested the permeability of the PaTp-TMC / PES membrane obtained in Example 1 in HCl / KCl solution systems of different concentrations. The results are shown in Table 4 below.
[0064] Table 4
[0065] HCl / KCl solution concentration (M) <![CDATA[H + / K + Select ratio]]> <![CDATA[H + Permeation flux (mol m -2 h -1 )]]> 1 451 6.72 0.5 478 1.94 0.25 226 0.48 0.1 54 0.13
[0066] The results showed that the proton permeation rate and H + / K + The selectivity increases in the range of HCl / KCl solution concentration from 0.1M to 0.5M. When the concentration increases to 1M, the selectivity increases. + The permeate flux increased significantly, while the selectivity decreased slightly but still maintained a high selectivity. + The performance results of permeate flux and selectivity were optimal when the concentration of HCl / KCl feed solution was 1M.
[0067] Test Example 2: Electrical Test
[0068] The ion transport properties across the membrane were measured using a Keithley 2450 source meter in the voltage range of -1.0 to 1.0 V. The PaTp-TMC / PES membrane was placed between H-type cells, preferably measuring a membrane area of 3.14 mm 2 The current-voltage characteristics were recorded using a pair of Ag / AgCl electrodes. Subsequently, the IV curves were recorded in an electrolyte with a specific concentration gradient to obtain the osmotic energy output (power density) performance. Power density (P, W m -2 ) is calculated as shown in the following formula (II):
[0069] P=(I 2 ×R) / S (II)
[0070] Where I is the current (A), R is the resistance (Ω), and S is the membrane area (m 2 ).
[0071] To investigate the effect of the concentration gradient of the HCl / HCl solution system, this experiment tested the electrical properties of the PaTp-TMC / PES membrane obtained in Example 1 in HCl / HCl solution systems with different concentration gradients. The results are shown in Table 5 below.
[0072] Table 5
[0073] HCl / HCl concentration gradient M / M <![CDATA[Maximum power density (W m -2 )]]> 2 / 0.04 6.64 2 / 0.4 2.32 2 / 0.2 4.97 2 / 0.02 5.63 2 / 0.01 4.82
[0074] The results showed that when the concentration gradient increased from 5 times (2 / 0.4M) to 50 times (2 / 0.04M), the maximum power density gradually increased and reached a maximum value of 6.64W m at 50 times. -2 , the power density increases, indicating that the osmotic energy conversion efficiency is improved. If the concentration gradient continues to increase, the power density begins to decrease, so the preferred HCl / HCl concentration is 2 / 0.04M, that is, the proton concentration gradient on both sides of the osmotic cell is 50 times.
[0075] Test Example 3
[0076] The PaTp-TMC / PES membrane obtained in Example 1 was subjected to a simulated waste acid solution recovery and power generation performance test under the condition of a preferred concentration gradient of 2 / 0.04M. The specific steps are as follows:
[0077] (1) Preparation of simulated waste acid solution: The simulated waste acid solution was prepared based on the "acid copper extraction" method. Malachite ore powder (200 mg) was dissolved in H2SO4 (2.5 M, 50 mL) and heated at 70 °C for 500 r min. -1 The mixture was stirred at a speed of 2 h. Then, the solution was cooled to room temperature and filtered to remove the precipitate. The filtrate was collected and used as a waste acid simulation solution;
[0078] (2) adjusting the pH of the original waste acid solution so that the proton concentration on both sides is 2M / 0.04M;
[0079] (3) The power generation test process is carried out according to the steps in Test Example 2. The actual picture of the test device is shown in Figure 7 ;
[0080] (4) After the power generation test, the permeation test was carried out according to the steps in the test example (the state changes of the solution system are as follows Figure 8 ) and calculate the ion permeation rate.
[0081] The performance test results of the covalent organic framework membrane used for waste acid recovery and power generation in the present invention are shown in Fig. 9The maximum power density is close to 4.5W m -2 While maintaining H + With heavy metal ions (representatively Cu 2+ ) high selectivity (selectivity 7516), reflecting the great application value of the present invention in realizing osmotic energy power generation while realizing waste acid recovery.
[0082] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a covalent organic framework membrane that can be used for waste acid recovery and power generation, characterized in that: The following steps are involved: (1) Pa was dissolved in ultrapure water to obtain solution A, and Tp and TMC were dissolved in n-hexane to obtain solution B and solution C respectively; (2) Solution A is dropped onto the surface of the PES membrane to form a Pa layer; Then solution B was added dropwise to react with Pa to form a Pa Tp composite layer; Finally, solution C was added dropwise to react with the Pa Tp composite layer to form a Pa Tp-TMC membrane, and the excess solution was removed; (3) solidification to obtain a covalent organic framework membrane that can be used for waste acid recovery and power generation and is stored in ultrapure water.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass fraction of Pa in the solution A is 1-3%, the mass fraction of Tp in the solution B is 0.01-0.1%, and the mass fraction of TMC in the solution C is 0.1-0.3%.
3. The preparation method according to claim 1, characterized in that: In step (2), before adding solution A, the PES membrane is soaked in ultrapure water, and the soaking time is 12-36 hours.
4. The preparation method according to claim 1, characterized in that: In step (2), the volume ratio of solution A, solution B and solution C is (12-18):(7-13):(7-13).
5. The preparation method according to claim 1, characterized in that: In step (2), the residence time of solution A on the surface of the PES membrane is 10-40 s; the reaction time of solution B with Pa is 5-15 s; and the reaction time of solution C with the Pa Tp composite layer is 10-40 s.
6. The preparation method according to claim 1, characterized in that: In step (3), the curing temperature is 70-90° C., and the curing time is 3-7 min.
7. A covalent organic framework membrane that can be used for waste acid recovery and power generation, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.
8. The covalent organic framework membrane for waste acid recovery and power generation according to claim 7, characterized in that: include: A PES membrane substrate, and a PaTp-TMC membrane formed by forming a PaTp composite layer on the surface of the substrate through Pa and Tp and then being modified by TMC.
9. The covalent organic framework membrane for waste acid recovery and power generation according to claim 7, characterized in that: The thickness of the Pa Tp-TMC film is 0.5-3.5 μm.
10. The use of the covalent organic framework membrane for waste acid recovery and power generation according to any one of claims 7 to 9, characterized in that: Including using it for the recovery of waste acid and power generation.
Citation Information
Patent Citations
Cross-linked covalent organic framework desalination membrane as well as preparation method and application thereof
CN112973460A